2019
DOI: 10.4103/heartviews.heartviews_32_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lipid abnormalities and cholesterol target value attainment in patients with stable and acute coronary heart disease in the United Arab Emirates

Abstract: Background: Careful management of lipid abnormalities in patients with coronary heart disease (CHD) or an acute coronary syndrome (ACS) can reduce the risk of recurrent cardiovascular events. The extent of hyperlipidemia in these very high-risk patients in the United Arab Emirates (UAE), along with the treatment strategies employed, is not clear. Methods: The Dyslipidemia International Study II was a multinational observational analysis carried out from 2012 to 2014. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The Weqaya program in Abu Dhabi reported dyslipidemia rates to be high (44.2%), with newly diagnosed individuals having high LDL and low HDL levels. The low HDL levels were reported to be a greater contributor to dyslipidemia than the high LDL levels [14].…”
Section: Dyslipidemiamentioning
confidence: 99%
“…The Weqaya program in Abu Dhabi reported dyslipidemia rates to be high (44.2%), with newly diagnosed individuals having high LDL and low HDL levels. The low HDL levels were reported to be a greater contributor to dyslipidemia than the high LDL levels [14].…”
Section: Dyslipidemiamentioning
confidence: 99%
“…These results came in accordance with Mellor et al, who defined type 2 diabetes mellitus as a condition of hyperglycemia associated with suppressed HDL cholesterol 24 . Also, Al Mahmeed et al, reported that hyperlipidemia was widely spread in patients with CHD 25 .…”
Section: Sensitivitymentioning
confidence: 99%
“…Similarly the Dyslipidemia International Study (DYSIS)‐Middle East registry showed that 61.8% of very high‐risk patients (T2DM with atherosclerotic cardiovascular disease [ASCVD]) failed to achieve control of cardiometabolic risk factors 12 . Moreover, the DYSIS‐II showed a progressive increase in the incidence of T2DM and simultaneously challenges in glycemic and cardiometabolic risk factor control in this growing population 13 . To identify the current challenges for the management of cardiorenal complications in T2DM in MENA and AFR, we convened a panel of experts to provide insights on the regional gaps with strategic recommendations for treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Moreover, the DYSIS‐II showed a progressive increase in the incidence of T2DM and simultaneously challenges in glycemic and cardiometabolic risk factor control in this growing population. 13 To identify the current challenges for the management of cardiorenal complications in T2DM in MENA and AFR, we convened a panel of experts to provide insights on the regional gaps with strategic recommendations for treatment. In addition, we aimed to foster the development of real‐world evidence that can support patients with T2DM, encourage patient‐centric projects for cardiorenal complications, and improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%